Profil Lifelong Learning siswa Madrasah Aliyah Negeri Demak - Soleh, Ahmad; Dewi, Endah Rita Sulistya; Hayat, Muhammad Syaipul (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Study This aim For know profile literacy Demak State Madrasah Aliyah students . Study This is type study descriptive qualitative . Deep sample study This is student Class XI MIPA Madrasah Aliyah Negeri Demak has 71 students . Data collection techniques use non - tests given to subject study about learning lifetime life ( lifelong learning ) includes five indicators namely : thinking complex , processing information , communication effectiveness , collaboration , and habits of mind . Research data analyzed in a way descriptive based on criteria score achievement each indicator learning lifetime life . Research result show that on components think complex obtained an average score of 40.20%, ( less ), processing information 55.60%, ( enough ), communication effective 66.61% ( good ), collaboration 73.38% ( good ), and habits of mind 32.20% ( poor ). Think complexes and habits of mind literacy needs to be increased environment MAN Demak students will be very good.